(untitled) (Bangladesh Journal of Plant Taxonomy, 2022)
A total of 209 species were documented where 181 species were used against 379 diseases/ailments from a village common forest of Rangamati, Bangladesh. Leaves were reported as most utilized plant part while herbs were dominant. Diversity indices revealed that the study area was rich in diverse medicinal plants. Collected voucher specimens were deposited in the Chittagong University Herbarium with an accession number. Bangladesh J. Plant Taxon. 29(1): 109-128, 2022 (June)